Política exterior y promoción económica internacional: hacia una nueva diplomacia económica - Bernal Rodríguez, José Luis (Revista Mexicana de Política Exterior, 2022)
The author discusses Mexico’s new foreign policy strategies. He acknowledges that without being unaware of the basic principles that have given our country prestige on the international stage, today theState Department is pursuing a more active foreign policy that includes protecting human rights and democracy, and promoting Mexicans’ rights abroad and the country’s participation in international organizations. He also highlights the work of the new economic diplomacy, that is endeavoring to take advantage of the infrastructure and experience of the Mexican Foreign Service around the world, coordinated by the new Office of the Undersecretary of Economic Affairs and International Cooperation which aspires to become an instrument that will allow the country to maximize the opportunities and address the challenges offered by the economic liberalization and trade agreements Mexico has signed.